THE RELATIONSHIP BETWEEN STRESS LEVELS AND BLOOD PRESSURE AMONG PRODUCTIVE-AGE ONLINE MOTORCYCLE TAXI DRIVERS IN BANDUNG CITY - Indah Tiara Novelia; Herdiman Herdiman (rifascholarpublisher.com, 2026)
Background: Hypertension is a major global health issue influenced by various factors, including stress. Online motorcycle taxi drivers are part of the productive-age workforce vulnerable to stress due to job uncertainty, long working hours, and exposure to traffic. Purpose: This study aims to analyse the relationship between stress levels and blood pressure among productive-age online motorcycle taxi drivers in Bandung City. Methods: This quantitative study employed a cross-sectional design involving 147 respondents selected through random sampling. Data were collected using demographic questionnaires, the Perceived Stress Scale (PSS-10), and blood pressure measurements via digital sphygmomanometer. Data were analysed using univariate and bivariate methods, including Spearman’s rank and Chi-square tests. Results: The study showed that the majority of respondents were male (91.8%) with an average age of 28 years, and 76.9% were smokers. Most respondents (92.5%) experienced moderate stress. Regarding blood pressure, 53.1% were in the prehypertension category, and 40.1% were in stage 1 hypertension. A significant positive correlation was found between stress level and systolic blood pressure (p < 0.001; r = 0.462), and diastolic blood pressure (p = 0.002; r = 0.258). Smoking behaviour and hypertension history also showed significant relationships with blood pressure. Conclusion: Stress levels are significantly associated with increased systolic and diastolic blood pressure in online motorcycle taxi drivers. These findings highlight the need for stress management and lifestyle interventions to prevent hypertension in informal sector workers. Keywords: Stress, blood pressure, hypertension, online motorcycle taxi drivers, productive age